Communication with partially verifiable information: An experiment - Valeria Burdea; María Montero Mu\~noz; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2020)
We use laboratory experiments to study communication games with partially verifiable information. In these games, based on Glazer and Rubinstein (2004, 2006), an informed sender sends a two-dimensional message to a receiver, but only one dimension of the message can be verified. We compare a treatment where the receiver chooses which dimension to verify with one where the sender has this verification control. We find significant differences in outcomes across treatments. However, receivers' payoffs do not differ significantly across treatments, suggesting they are not hurt by delegating verification control. We also show that in both treatments the receiver's best reply to senders' observed behavior is close to the optimal commitment strategy identified by Glazer and Rubinstein.
Keywords: 330; communication; partially verifiable messages; verification control; experiment